COVID-19, liquidity and financial health: Empirical evidence from South Asian economy - Md. Rezaul Karim; Samia Afrin Shetu; Sultana Razia (Asian Journal of Economics and Banking (AJEB), 2021)
Purpose - The pandemic COVID-19 has affected every sector of an economy in every possible way. Banking sector of Bangladesh has been affected by it badly. The purpose of this paper is to find out the impact of COVID-19 on the liquidity and financial health of the listed banks in Bangladesh. Design/methodology/approach - Liquidity ratios are calculated to measure the liquidity condition of the banks and revised Altman's Z-Score Model for non-manufacturing companies is used to measure the financial health. The ratios are compared before and during the COVID-19 periods to assess the impact. Findings - The findings of this study indicate a deterioration of liquidity position and financial health of the listed banks after the emergence of this pandemic. Though the banks have poor liquidity ratios and financial health prior to the emergence of this pandemic, they have decreased more in the second quarter of 2020. Most of the banks have poor liquidity ratios and cash position. The listed Islamic Banks have poor financial health than the listed Commercial Banks and all the banks belong to the red zone in all the quarters. Practical implications -The results of this study will have policy implications for companies and regulators of money market. Originality/value - This paper is a pioneer initiative in assessing the impact of COVID-19 pandemic on liquidity and financial health based on empirical data.
Keywords: 330; COVID-19; Liquidity; Financial health; Z-Score